2014
DOI: 10.1186/1757-7241-22-6
|View full text |Cite
|
Sign up to set email alerts
|

Accidental cold-related injury leading to hospitalization in northern Sweden: an eight-year retrospective analysis

Abstract: BackgroundCold injuries are rare but important causes of hospitalization. We aimed to identify the magnitude of cold injury hospitalization, and assess causes, associated factors and treatment routines in a subarctic region.MethodsIn this retrospective analysis of hospital records from the 4 northernmost counties in Sweden, cases from 2000-2007 were identified from the hospital registry by diagnosis codes for accidental hypothermia, frostbite, and cold-water drowning. Results were analyzed for pre-hospital sit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
38
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 29 publications
4
38
0
Order By: Relevance
“…A further neuroprotective mechanism may be the reduction of hyperglycolysis associated with ethanol exposure following TBI [10]. Ethanol may lead to a decrease in body temperature and this may have a neuroprotective effect [18]. Finally, ethanol decreases conscious state and, thus, patients with mild head injury may present as deeply comatose and meet the criteria for severe TBI where assessment of TBI severity is made by clinical state rather than anatomical or CT scan features.…”
Section: Introductionmentioning
confidence: 98%
“…A further neuroprotective mechanism may be the reduction of hyperglycolysis associated with ethanol exposure following TBI [10]. Ethanol may lead to a decrease in body temperature and this may have a neuroprotective effect [18]. Finally, ethanol decreases conscious state and, thus, patients with mild head injury may present as deeply comatose and meet the criteria for severe TBI where assessment of TBI severity is made by clinical state rather than anatomical or CT scan features.…”
Section: Introductionmentioning
confidence: 98%
“…The following data refer to the general population and are not specific to sport or recreation. The estimated incidence of accidental hypothermia in the general population ranges from approximately 1‐5 cases per 100 000 inhabitants per year in European countries and 5.6 per 1 million persons per year in the USA . The annual incidence of fatal cases may be higher in rural compared to urban areas .…”
Section: Epidemiology: Estimating Incidence and Mortality Of Accidentmentioning
confidence: 99%
“…Thus, data reflect only those cases requiring hospitalization (or deaths) and do not account for less severe cases not requiring hospitalization or undiagnosed cases of hypothermia. Studies have shown that mild and moderate hypothermia account for a considerable proportion of all cases of hypothermia . Secondly, because data are often collected retrospectively and filtered using the International Classification of Diseases diagnosis codes, only those cases for which hypothermia is documented as such can be retrieved.…”
Section: Epidemiology: Estimating Incidence and Mortality Of Accidentmentioning
confidence: 99%
See 2 more Smart Citations